Mana : a history of a western category - Meylan, Nicolas. (Supplements to Method & Theory in the Study of Religion, 2017)
In Mana: A History of a Western Category Nicolas Meylan proposes a critical account of Western imaginations of mana, a word belonging originally to Oceanic languages but borrowed by European languages in which it acquired the meaning 'supernatural power.' While mana is best known for its tenure in the disciplines studying religion, Nicolas Meylan situates such academic uses in a wider context, analyzing the ways Westerners conceptualized mana in the earlier colonial context as well as its mobilizations in the late 20th and early 21st centuries by (video)game designers and Neo-Pagan witches. This focus on various Western uses of mana allows for the critical investigation of the ways power has been mystified in conjunction with religion.